Assessment of bone marrow angiogenesis using F VIII-related antigen and its relationship to proliferating cell nuclear antigen (PCNA) in multiple myeloma. - AL- Mudallal, Subh S. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Multiple myeloma (MM) is a malignant clonal expansion of plasma cells. Previous studies had demonstrated that both bone marrow angiogenesis as measured by microvessel density (MVD) and PCNA were increased in variety of malignant disorders, including multiple myeloma.Objective: Assessment of angiogenesis in bone marrow of MM patients by using immunohistochemical stain to measure microvessel density (MVD) using factor VIII –related antigen and to evaluate the expression of PCNA antigen in plasma cells of MM bone marrow sections . Also to find the correlation between these two parameters and between them and the percentage of plasma cells infiltration in bone marrow of MM.Patients, materials and methods: This retrospective study was conducted from May 2007 to Jaunary 2008 on 37 bone marrow biopsies diagnosed as multiple myeloma, along with 10 age matched control subjects who had reactive plasmacytosis of less than 10% in their bone marrow. The cases were retrieved from recording archive files of Department of Pathology in the Teaching Laboratory of Medical City Hospital, laboratory of Al- Yarmouk hospital and AL-Yarmouk National Center of Haematology. Three sections were taken from each formalin fixed paraffin embedded bone marrow trephine biopsy of MM and of control cases. One representative section was stained with Hematoxylin and Eosin (H&E), while the other two sections were stained immunohistochemically for factor VIII-related antigen as an endothelial cell marker, and for PCNA as an indicator of the proliferative state of myeloma cells All stained sectionswere examined by light microscopy and the mean vessel density (MVD) was estimated and was used for statistical analysis. For immunostained PCNA cells, the labeling index scoring system of Alves et al was adopted for estimating the percentage of positive nuclear staining.Results: This study revealed that there was a significant increase in bone marrow angiogenesis and in the expression of PCNA in plasma cells of patients with multiple myeloma compared to control cases. Moreover this study showed that PCNA correlated significantly with bone marrow microvessel density and both parameters correlated significantly with the percent of plasma cell in the bone marrow of patient with multiple myeloma.Conclusion : Both PCNA and angiogenesis as expressed by MVD were increased in multiple myeloma and both of them correlated with the percentage of plasma cell infiltration which reflected the activity of the disease .Moreover the proliferative activity of plasma cell as represented by PCNA expression was closely related to angiogenic activity , thus it can be proposed that both markers reflect the disease activity and they may provide additional information when included in the initial evaluation of myeloma bone marrow biopsies .